Touchpoints: parents and nurses perceptions and satisfaction - Soares,Hélia (2016)
Support provided to families experiencing parenting should be based on a trust relationship between nurses and parents. Satisfaction experienced with the process of care, both by parents and nurses, assumes great relevance and can be considered as an outcome of nursing care. Purpose: To understand the experience and meaning given by parents and nurses of participating in the implementation of an innovative nursing intervention, with Touchpoints (TP) methodology, of parents of children, from 11 to 24 months, and of nurses. Study Design and Methods: Qualitative study using a phenomenological approach. Data collection was performed using (i) field-notes (FN) written by the nurses who implemented the TP methodology and (ii) focus groups (FG) with 10 parents of children from the intervention group. Results: Parents considered that the TP sessions implemented by nurses contributed to: Acquisition of knowledge and skills; Validation of parental practices; Improvement of child behavior; Parental confidence; Interpersonal relationship; Professional competences; Specific competences; Satisfaction. Participant nurses perceived that the TP methodology contributed to: Mobilization and application of TP principles; Learning process; Parents interest; Feelings/emotions; Satisfaction. Clinical Implications: Nurses caring for families should implement innovative methodologies that facilitate adaptation to parenting, such as Touchpoints. Implementing the TP methodology contributed to parents and nurses satisfaction.